Late-Holocene coastal depositional environments and climate changes in the Gulf of Corinth, Greece - Emmanouilidis, Alexandros; Unkel, Ingmar; Triantaphyllou, Maria; Avramidis, Pavlos (The Holocene, 2020)
Multidisciplinary studies in coastal systems of the eastern Mediterranean region have proven to be excellent tools in understanding paleoenvironmental, paleoecological, and paleoclimatic changes that took place during the Holocene period, and how these changes interacted with urban development and growth. This paper presents sedimentological, high-resolution x-ray fluorescence (XRF scanning), micropaleontological, and x-ray diffraction (XRD) data from three shallow sediment cores that were retrieved from Aliki (ancient Siphai or Tipha) salt pond. The study area is located in a unique, highly tectonic geographical region, at the northeast part of the Gulf of Corinth in Greece. Beachrock deposits that form a barrier between the salt pond and the marine environment seem to play an important role in the evolution of the area. The chronological framework was set at around 3100 cal. BP by four 14C radiocarbon dates, and the evolutionary model that was established indicates four different changes taking place during this period at the study area. From around 3100 to 1600 cal. BP, a transition from a closed to an open lagoonal environment was identified, interrupted by a fluvial terrestrial deposit at around 2500 cal. BP. A shift toward a closed lagoonal system at around 1600 cal. BP and the establishment of a salt pond environment seem to correlate with tectonic activity. The study provides important information about the evolution of coastal landscape in such a tectonic active region and points the interaction between regional human activity and climatic changes during the late-Holocene period.
Online veröffentlicht: 18. September 2019
Gesehen am 17.02.2025